MDR Pumps as Crossroads of Resistance: Antibiotics and Bacteriophages - Pavel A. Nazarov (MDPI AG, 2022)
At present, antibiotic resistance represents a global problem in modern medicine. In the near future, humanity may face a situation where medicine will be powerless against resistant bacteria and a post-antibiotic era will come. The development of new antibiotics is either very expensive or ineffective due to rapidly developing bacterial resistance. The need to develop alternative approaches to the treatment of bacterial infections, such as phage therapy, is beyond doubt. The cornerstone of bacterial defense against antibiotics are multidrug resistance (MDR) pumps, which are involved in antibiotic resistance, toxin export, biofilm, and persister cell formation. MDR pumps are the primary non-specific defense of bacteria against antibiotics, while drug target modification, drug inactivation, target switching, and target sequestration are the second, specific line of their defense. All bacteria have MDR pumps, and bacteriophages have evolved along with them and use the bacteria's need for MDR pumps to bind and penetrate into bacterial cells. The study and understanding of the mechanisms of the pumps and their contribution to the overall resistance and to the sensitivity to bacteriophages will allow us to either seriously delay the onset of the post-antibiotic era or even prevent it altogether due to phage-antibiotic synergy.